Footprinting for fingerprinting: proof-of-concept for the use of hydroxyl radical protein footprinting for structural comparison studies - Vanessa A. Noreika; Aaron T. Wecksler (mAbs, 2025)
Monoclonal antibodies (mAbs) require extensive physicochemical characterization to ensure product quality. The clinical and pharmacological properties of mAbs are linked to higher order structure (HOS), but high-resolution analytical techniques to evaluate structural conformations and structural comparisons during drug design and process development are limited. Here, we provide proof-of-concept for the use of hydroxyl radical footprinting-mass spectrometry (HRPF-MS) to characterize the average solvent accessible surface area ( < SASA>) of mAbs. The premise is that each mAb exhibits a unique “oxidative footprint” that may aid in demonstrating structural similarities and differences between mAbs and support the HOS characterization of a biotherapeutic fingerprint. This work, which includes case studies for comparing oxidative footprints between mAbs, highlights the challenges and future state needed to realize the potential of HRPF for the application of biotherapeutic fingerprinting.